2016
DOI: 10.1002/hbm.23250
|View full text |Cite
|
Sign up to set email alerts
|

fMRI study of neural sensitization to hedonic stimuli in long‐term, daily cannabis users

Abstract: Although there is emergent evidence illustrating neural sensitivity to cannabis cues in cannabis users, the specificity of this effect to cannabis cues as opposed to a generalized hyper‐sensitivity to hedonic stimuli has not yet been directly tested. Using fMRI, we presented 53 daily, long‐term cannabis users and 68 non‐using controls visual and tactile cues for cannabis, a natural reward, and, a sensory‐perceptual control object to evaluate brain response to hedonic stimuli in cannabis users. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 26 publications
5
64
2
2
Order By: Relevance
“…A significant dose-response relationship was found in cuneus activity at follow-up, where greater deactivation was associated with greater cannabis use. These results are consistent with work demonstrating differential cuneus activation between abstinent adolescent marijuana users and control subjects (11) and adult daily marijuana users and control subjects (33). Furthermore, a recent pharmacological fMRI study showed that cuneus activity is modulated by THC administration (34).…”
Section: Discussionsupporting
confidence: 90%
“…A significant dose-response relationship was found in cuneus activity at follow-up, where greater deactivation was associated with greater cannabis use. These results are consistent with work demonstrating differential cuneus activation between abstinent adolescent marijuana users and control subjects (11) and adult daily marijuana users and control subjects (33). Furthermore, a recent pharmacological fMRI study showed that cuneus activity is modulated by THC administration (34).…”
Section: Discussionsupporting
confidence: 90%
“…For example, recent studies reflect that the OFC may underlie neural sensitivity to cannabis cues 65 and place individuals at greater risk for a more protracted trajectory of use, particularly when youth begin using at an earlier age 66 . Further, OFC dysregulation appears to be a signature feature across anxiety, OCD, and anorexia nervosa 6769 , subsequently indicating its relevance as a marker of neural health, and potentially, a region that may be disrupted during the transition into emergent or more long-standing psychiatric conditions.…”
Section: Discussionmentioning
confidence: 99%
“…If compared with nonusers, long-term cannabis users were demonstrated to have greater brain activity during cannabis cues relative to natural reward cues (ie, fruit itself being superior to neutral cues) in the orbitofrontal cortex, striatum, anterior cingulate gyrus, and ventral tegmental area 72. The users had positive correlations between neural response to cannabis cues in the fronto-striatal-temporal regions and subjective craving, cannabis-related problems, serum levels of THC metabolites, and the intensity of CWS.…”
Section: Human Biological Backgroundmentioning
confidence: 99%
“…The users had positive correlations between neural response to cannabis cues in the fronto-striatal-temporal regions and subjective craving, cannabis-related problems, serum levels of THC metabolites, and the intensity of CWS. All of which were not found in non-cannabis users,72 suggesting a sensitization and specificity of the brain response to cannabis cues in long-term cannabis users 72…”
Section: Human Biological Backgroundmentioning
confidence: 99%